Organizational Challenges of Leadership in a Healthcare Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the appropriate leadership style in a healthcare organization, and what are the qualities of a successful leader in a healthcare organization?Purpose: The purpose of the research was to conduct a review of foreign professional literature in which the authors addressed leadership in healthcare organizations.Method: A review of foreign professional literature was conducted in the Elsevier and PubMed databases, where we searched for free accessible scientific articles. We identified 92 articles in the Elsevier database and 176 articles in the PubMed database, totaling 268 articles. After the screening phase, we included 100 abstracts in the research, which we reviewed. We incorporated 11 articles available in full text and analyzed them. Based on inclusion and exclusion criteria, 7 articles were selected for final review and analysis.Results: Soft leadership styles predominate, which are based on emotional intelligence, communication, empathy, and interaction between the leader and employees. Further development in leadership contributes to the employee's expanded knowledge, not only of leadership, but also of a clear vision for their career path, organizational vision, and employee engagement. An individual can choose the leadership style that is most appropriate for the current context and people. Leadership reflects the leader and the goal to which they aim to direct their organization, and no single ideal leadership style is evident.Organization: The results of the research are valuable for both founders and managers in healthcare institutions. The collected data on leadership and leader characteristics can significantly contribute to improving patient care quality and enhancing organizational performance.Society: The article describes the essence of leadership in a healthcare organization, which should include all stakeholders, such as leaders, patients, and all employees. Effective management relies on people and is built on trust and respect, which is achieved not through anarchy but through persistence, understanding, and unity. It is essential to create an environment in each organization that allows stakeholders to co-create changes, participate in its development, thereby improving their career paths and enhancing the quality of both: the employees and the users.Originality: The results of the literature review indicated various leadership styles, but they all shared a common focus on people-oriented leadership in healthcare organizations.Limitations/Future Research: We included articles published in the past three years (from 2022 to 2024) in which the authors researched leadership in nursing and medical care within healthcare organizations. It would be beneficial to more precisely define leadership across different institutions, taking into account the specific needs of users.
Keywords: organization; healthcare; leadership; leadership styles; qualities of a leader